Anticholesterol Activity of Combined Binahong and Keji Beling Leaf Extracts in Mice (Mus musculus) - Rizky, Eka Septia Nur; Aina, Ganea Qorry; Kusumawati, Nursalinda; Farpina, Eka (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Cholesterol is a type of lipid found in the human body, with approximately 80% produced endogenously by the liver and the remaining 20% obtained from dietary sources. Elevated total cholesterol levels in the blood increase the risk of various health conditions such as cardiovascular disease, obesity, hypertension, and even stroke. Prolonged elevation can lead to plaque formation in blood vessels, resulting in impaired circulation and potentially life-threatening complications. The use of synthetic cholesterol-lowering drugs is often associated with unwanted side effects, including liver toxicity, muscle pain, and gastrointestinal disturbances. This has prompted increasing interest in safer, natural alternatives such as herbal medicine, which is perceived to provide fewer side effects and additional health benefits. This study aimed to investigate the anti-cholesterol activity of a combination of Binahong (Anredera cordifolia) and Keji Beling (Strobilanthes crispus) leaf extracts in mice (Mus musculus) induced with a high-cholesterol diet. The extraction method employed was maceration, using 96% ethanol as the solvent to ensure optimal phytochemical yield. The experimental design consisted of five groups: a negative control group, a positive control group, and three treatment groups receiving combinations of Binahong and Keji Beling extracts in ratios of 1:1, 1:3, and 3:1. Total cholesterol levels were measured using the Point of Care Test (POCT) method. The results showed that all treatment groups experienced a significant reduction in total cholesterol levels (p = 0.001 < 0.05). The most effective reduction was observed in the 1:1 ratio group, with a decrease of 45.39%, followed by the 3:1 group (27.80%) and the 1:3 group (14.17%). These findings indicate strong potential for development as an effective and safe herbal alternative for lowering cholesterol levels.